Proposition of adjustments to the ACMG‐AMP framework for the interpretation of MEN1 missense variants. Issue 6 (28th March 2019) - Romanet, Pauline; Odou, Marie‐Françoise; North, Marie‐Odile; Saveanu, Alexandru; Coppin, Lucie; Pasmant, Eric; Mohamed, Amira; Goudet, Pierre; Borson‐Chazot, Françoise; Calender, Alain; Béroud, Christophe; Lévy, Nicolas; et al.
Abstract: In 2015, the ACMG‐AMP guidelines provided a general procedure for the objective and reproducible classification of genomic variants. While the benefits of this framework are of major importance, its adaptation for locus‐specific use is needed. Multiple Endocrine Neoplasia type 1 (MEN1) occurs due to inactivating mutations in the tumour suppressor gene MEN1, including 20% of missense variants. The classification of these variants may be extremely challenging. Here, we compared the interpretation of the 122 MEN1 missense variants, identified in the French population over the past 15 years by the TENGEN network (French oncogenetics network of neuroendocrine tumors) versus by using the ACMG‐AMP guidelines, and analyzed the causes of discordance. A total of 59.8% of missense variants were termed as (likely)‐pathogenic variants by TENGEN versus only 28.7% using ACMG‐AMP guidelines. Actually, 53.4% (39/73) of TENGEN (likely)‐pathogenic variants were declassified in variant of uncertain significance (VUS) by using ACMG‐AMP guidelines, thereby affecting the clinical management of patients and their families. Twenty of these ACMG‐AMP VUS were found in patients with a clinically authentic MEN1 disease. Here, TENGEN proposes adjustments to the ACMG‐AMP framework for the interpretation of MEN1 missense variants. These propositions merge both the classification systems, and are particularly interesting, as MEN1 is included in the ACMG secondary findings list for reporting in clinical genomic sequencing. Abstract : We compared the interpretation of 122 MEN1 missense variants, identified in 370 patients with Multiple Endocrine Neoplasia type 1 (MEN1) from the French population over the past 15 years by the TENGEN group (French oncogenetics network of neuroendocrine tumors) versus by using the ACMG‐AMP guidelines, and analyzed the causes of discordance. Then, TENGEN proposes adjustments to the ACMG‐AMP framework for the interpretation of MEN1 missense variants.